Perceptions of Trade Credit Insurance Value : Malaysian Evidence - Wong, Benny Weng Hong (2013)
Trade credit insurance (“TCI”) is a subject unfamiliar to most companies in Malaysia despite being around for more than a decade. This is not surprising considering the penetration rate of only 3.84% in Malaysia. The main aim of this paper is to examine the Malaysian firm‟s perceptions of TCI value and the TCI value drivers to help credit insurance companies uncover the motivational factors according to firm size and profit margin in order to improve the penetration rate in Malaysia. Furthermore, the results of this paper could also provide existing users of TCI in Malaysia an insight towards optimizing the usage of this instrument through studies conducted on their industry peers. The research method would draw on an adaptation of Zammit, Ross & Wood (2009) questionnaire as a benchmark for the rest of the study. 135 firm survey of how existing users of TCI perceive the value of often-cited attributes of TCI and multiple regression analysis to create a model of TCI value drivers. Most TCI value is derived from the increased trade sales experienced through protection of TCI, ability to set competitive terms and improved access to trade finance. Distinct differences could be observed in perceived TCI value between larger and smaller firms as well as between higher and lower profit margin firms. This paper would then provide the foremost evidence of perceived TCI value to Malaysian companies and credit insurers.